Chapter 7 Introduction to the Section: On the Manifestations and Consequences of Ageism (2018)
This introductory section outlines the various ways in which ageism is manifested. Specifically, we discuss ageism as an individual occurrence that impacts the life of each and every one of us. Ageism also manifests at the societal level and thus, impacts society at large. The chapters in this section address ageism in young and old. Chapters discuss ageism in the health and mental health systems, in the media and in immigration policies. The breadth and depth at which ageism impacts our lives provide a direct call for action.